Earth and Space: Photographs from the Archives of NASA - Nirmala Nataraj (Chronicle Books, 2015)
Take a tour of the universe with this breathtaking collection of photographs from the archives of NASA. Astonishing images of Earth from above, the phenomena of our solar system, and the celestial bodies of deep space will captivate readers and photography lovers with an interest in science, astronomy, and the great beyond. Each extraordinary photograph from the legendary space agency is paired with explanatory text that contextualizes its place in the cosmic ballet of planets, stars, dust, and matter—from Earth's limb to solar flares, the Jellyfish Nebula to Pandora's Cluster. Featuring a preface by Bill Nye, this engaging volume offers up-close views of our remarkable cosmos, and sparks wonder at the marvels of Earth and space